Uma abordagem baseada em conhecimento para apoio ao combate às perdas comerciais na distribuição de energia elétrica - Dias, Hélder Bergamin Pimentel (2006)
Frauds and measure failures in Power Distribution cause great losses to Power Companies. A traditional way to combat these problems is performing field inspections on customers. However, selecting customers to be inspected is a difficult task for experts on such domain. The goal of the present work is to analyze such knowledge and propose a knowledge based system able to acquire, modify and apply heuristics obtained from the experts on the customer selection process. The system used a real customer database of the local power distribution company for selecting customers for inspection. The evaluation of the results was carried out through two different strategies: executing real field inspections on the selected customers and comparing the results with previously performed field inspections.